From Biology to Linguistics: The Definition of Arthron in Aristotle's Poetics - Laspia, Patrizia (UNIPA Springer Series,, 2018)
This book attempts to solve Aristotle's definition of arthron in the XX chapter of the Poetics by seeing it in a new light. This definition has always been considered an unsolvable problem. Starting with a detailed analysis of the Greek text, and of the various attempts to emend the text in order to make sense of it, the book provides an analytical description of the critical literature, showing that the solutions proposed up to now need to be revised. The possible solution is found in viewing the XX chapter of the Poetics not as a classification of parts of speech, as it was usually supposed, but by considering the biological definitions of arthron in Aristotle's corpus. This leads to the conclusion that, in linguistics as well as in biology, arthron is a "joint". In this light, the book offers a new textual conjecture for the first example of arthron in the Poetics.